China's reforms at 30 : challenges and prospects - Yang, Dali L.; Zhao, Litao, 1972- (Series on contemporary China, 2009)
This book consists of papers presented at the International Conference on "China : The Next Decade", organized by the East Asian Institute at the National University of Singapore in 2007 to commemorate the Institute's 10th anniversary. With eight papers covering China's economic, social and political development, this volume offers a balanced yet in-depth assessment of the challenges facing China in the next decade. Featuring contributions from internationally renowned scholars, this timely volume analyzes key aspects of China's reforms and development, such as the financial reform, international trade, leadership succession, social protests, health care reform and ethnic relationships. It is suitable for China scholars as well as advanced undergraduate and graduate students interested in China's polity, economy and society